Effect of women empowerment on women-owned business performance in Wakiso District, Uganda - Mbowa, Henry Stanley; Businge, Mbabazi Phelix; Ssemaluulu, Paul; Eton, Marus (Goodwood Publishing, 2023)
Purpose: This study identified women empowerment practices and investigated the challenges to women-owned business performance in the Kyengera Town Council. Research methodology: This study employed a descriptive survey design using a qualitative data collection approach. A sample of 57 women was selected from 67 women who owned businesses using Yamane’s formula. Data were collected through surveys and interviews, edited, cleaned, coded to develop themes, and entered into MS Excel to generate frequency tables. Results: The results showed economic empowerment, competence development, market information sharing, and social networking as practices for women’s empowerment. Furthermore, the results reveal economic issues, law and policy, environmental issues, sociocultural issues, geopolitics, and incompetence as key challenges. Limitations: The study was limited by financial challenges and inaccessibility to women-owned businesses on the Kyengera town council. Contribution: This study offers a new era for research on women’s empowerment, key to addressing the existing gap in women’s contribution to women-owned business performance. Thus, based on the results, women feel assured of their role in women-owned business performance and community development in the district. Novelty: The originality of the study was expressed in the results elicited from the participants. Such a study has never been conducted in the Kyengera Town Council; thus, the results would provide avenues for referral for future researchers. In previous studies, male businesses were at the forefront of other areas. However, women who owned businesses in the Kyengera council were considered for study.